PERLINDUNGAN HUKUM PEMEGANG HAK EKSKLUSIF MEREK ERG (STUDI KASUS PUTUSAN NOMOR 80/PDT.SUS-HKI/MEREK/2021/PN.NIAGA.JKT.PST) - Nurlela; Megawati Barthos (Fakultas Hukum Universitas Borobudur, 2023)
The high number of trademark disputes in a country arises from trademark registrations that should be considered invalid, such as trademarks that are similar or identical to trademarks registered by other people without approval. Based on this, this research will analyze Decision Number 80/Pdt.Sus-HKI/Merek/2021/PN.Niaga.Jkt.Pst. related to legal protection for the exclusive holder of the ERG brand and legal considerations from the judge in imposing sanctions on the defendant. The research method used to discuss this problem is normative juridical. The conclusion from the results of this research is that the plaintiff as the holder of exclusive rights to the ERG brand has received legal protection based on Article 1 number 5 in conjunction with Article 83 paragraph (1) of Law Number 20 of 2016 concerning Marks and Geographical Indications. The judge's legal considerations in imposing sanctions on the defendants were appropriate and in accordance with applicable legal provisions because the judge accepted the plaintiff's claim as the exclusive owner and legal owner of the ERG brand.